Drought stress and plant ecotype drive microbiome recruitment in switchgrass rhizosheath. Issue 10 (27th August 2021) - Liu, Tie‐Yuan; Ye, Nenghui; Wang, Xinyu; Das, Debatosh; Tan, Yuxiang; You, Xiangkai; Long, Mingxiu; Hu, Tianming; Dai, Lei; Zhang, Jianhua; Chen, Mo‐Xian
Abstract: The rhizosheath, a layer of soil grains that adheres firmly to roots, is beneficial for plant growth and adaptation to drought environments. Switchgrass is a perennial C4 grass which can form contact rhizosheath under drought conditions. In this study, we characterized the microbiomes of four different rhizocompartments of two switchgrass ecotypes (Alamo and Kanlow) grown under drought or well‐watered conditions via 16S ribosomal RNA amplicon sequencing. These four rhizocompartments, the bulk soil, rhizosheath soil, rhizoplane, and root endosphere, harbored both distinct and overlapping microbial communities. The root compartments (rhizoplane and root endosphere) displayed low‐complexity communities dominated by Proteobacteria and Firmicutes. Compared to bulk soil, Cyanobacteria and Bacteroidetes were selectively enriched, while Proteobacteria and Firmicutes were selectively depleted, in rhizosheath soil. Taxa from Proteobacteria or Firmicutes were specifically selected in Alamo or Kanlow rhizosheath soil. Following drought stress, Citrobacter and Acinetobacter were further enriched in rhizosheath soil, suggesting that rhizosheath microbiome assembly is driven by drought stress. Additionally, the ecotype‐specific recruitment of rhizosheath microbiome reveals their differences in drought stress responses. Collectively, these results shed light on rhizosheath microbiome recruitment in switchgrass and lay the foundation for the improvement of drought tolerance in switchgrass by regulating the rhizosheath microbiome. Abstract : The rhizosheath is beneficial for plant adaptation to drought. Four rhizocompartments of switchgrass harbored distinct and overlapping microbial communities. The rhizosheath displayed high‐complexity communities compared to the root compartments. Rhizosheath microbiome assembly is driven by drought stress and plant ecotype.